2014
DOI: 10.1186/1744-8603-10-42
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, determinants and systems-thinking approaches to optimal hypertension control in West Africa

Abstract: BackgroundIn West Africa, hypertension, once rare, has now emerged as a critical health concern and the trajectory is upward and factors are complex. The true magnitude of hypertension in some West African countries, including in-depth knowledge of underlying risk factors is not completely understood. There is also a paucity of research on adequate systems-level approaches designed to mitigate the growing burden of hypertension in the region.AimsIn this review, we thematically synthesize available literature p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 36 publications
(61 reference statements)
3
24
0
Order By: Relevance
“…Financial constraints are known to discourage initiation of care. [31][32][33] This factor is not limited to LMICs; lack of health insurance, lack of medication coverage, and higher costs are strong predictors of missing appointments among hypertensive patients in the United States. 27,34 In addition, poor adherence to antihypertensive medications has been associated with unaffordable drug prices.…”
Section: Discussionmentioning
confidence: 99%
“…Financial constraints are known to discourage initiation of care. [31][32][33] This factor is not limited to LMICs; lack of health insurance, lack of medication coverage, and higher costs are strong predictors of missing appointments among hypertensive patients in the United States. 27,34 In addition, poor adherence to antihypertensive medications has been associated with unaffordable drug prices.…”
Section: Discussionmentioning
confidence: 99%
“…[21] In Ethiopia community-based organizations have provided the vital link in improving patient retention in care within HIV care settings from 77% in 2004 to 92% in 2012 with minimum resources. [22] This may also assist in improving the performance of this indicator in Zimbabwe. Being part of a support group enables a patient to have a treatment supporting partner who would then help enhance adherence to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we speculate whether the rural vs urban difference in living conditions and lifestyle could modify the effect of some of the conventional risk markers for albuminuria in rural SSA. A recent review suggested that living in an urban SSA environment caused more physical and psychic stress in general than living in a rural setting . It is a possibility that ongoing exposure to physical and psychic stress could aggravate the chronic endothelial inflammation usually found in patients with hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review suggested that living in an urban SSA environment caused more physical and psychic stress in general than living in a rural setting. 13 It is a possibility that ongoing exposure to physical and psychic stress could aggravate the chronic endothelial inflammation usually found in patients with hypertension. HbA 1c level >53 mmol/mol corresponding to suboptimal or poor glycemic control was strongly associated with albuminuria.…”
Section: Discussionmentioning
confidence: 99%